2004
DOI: 10.1029/2003jc001794
|View full text |Cite
|
Sign up to set email alerts
|

On the influence of a surface coastal front on near‐inertial wind‐induced internal wave generation

Abstract: [1] A numerical model is used to examine the wind-induced near-inertial internal waves in the coastal region in the presence of a surface front. Initial calculations with the front separating a well-mixed coastal region from a stratified offshore area in an infinite sea domain showed that away from the front, surface inertial oscillations are dominant. Near the front on the positive vorticity side, superinertial internal waves are generated and propagate offshore in an analogous manner to that found when strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2004
2004
2005
2005

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 36 publications
(59 reference statements)
2
11
0
Order By: Relevance
“…They showed that nonlinear effects arising from the change in vorticity in the region of a frontal jet, (such as that associated with a dome) in combination with wind forcing of frequency x f (Xing and Davies 2003), produced internal wave generation on the stratified side of the front. If x f is super-inertial, then internal waves can propagate away from their generation region, although they can be trapped at depth due to sloping isotherms (Mooers 1975;Xing and Davies 2004a). At the sub-inertial frequency, they are trapped in their generation region (Davies and Xing, 2002).…”
Section: Introductionmentioning
confidence: 97%
“…They showed that nonlinear effects arising from the change in vorticity in the region of a frontal jet, (such as that associated with a dome) in combination with wind forcing of frequency x f (Xing and Davies 2003), produced internal wave generation on the stratified side of the front. If x f is super-inertial, then internal waves can propagate away from their generation region, although they can be trapped at depth due to sloping isotherms (Mooers 1975;Xing and Davies 2004a). At the sub-inertial frequency, they are trapped in their generation region (Davies and Xing, 2002).…”
Section: Introductionmentioning
confidence: 97%
“…This energy can be transferred to gravity waves in the ocean interior at frequencies (σ) just larger than f (1.00f < σ < 1.09f) when they propagate towards lower latitudes [ Garrett , 2001], or, when considered on a spherical shell, just smaller than f (σ ≈ 0.99f) towards higher latitudes [ Maas , 2001]. Near‐inertial waves can also propagate into the interior when generated via surface fronts [ Xing and Davies , 2004]. Internal gravity waves exist between f < σ < N, with f ≪ N = (−g/ρ∂ρ/∂z) 0.5 the buoyancy frequency of stable density (ρ) stratification and g denoting the acceleration of gravity in the negative z‐direction.…”
Section: Introductionmentioning
confidence: 99%
“…An along frontal jet with velocity v having a maximum of order 35 cm s −1 gave a region of positive vorticity η = 0.4 × 10 −4 s −1 to the west of the front with a maximum negative vorticity η = −1.0 × 10 −4 s −1 to the east. This choice of frontal parameters is arbitrary and taken to be consistent with Xing and Davies [2004].…”
Section: Numerical Model and Form Of Calculationsmentioning
confidence: 99%
“…In Craig's case there is no difference between sub‐ or super‐inertial frequencies which have the same value of ∣ω − f∣. However, in frontal regions non‐linear effects associated with the along front jet, lead to significant penetration of the wind's energy to depth [ Xing and Davies , 2004] and internal wave generation. Associated with these internal waves is the possibility of enhanced non‐linear interaction between them.…”
Section: Introductionmentioning
confidence: 99%